Analisis Pengaruh Experiential Marketing Terhadap Loyalitas Pelanggan ( Pada Starbucks Coffee Paragon Mall Surakarta ) - Ganaputri, Kania Rahmawati; , Basworo Dibyo, S.E, M.Si (2016)
This study was conducted to analyze the effect of variable Experiential Marketing as measured by several factors: the sense, Feel, Think, act, relate on customer loyalty in starbucks coffee paragon mall Surakarta. Data were collected through questionnaires method using purposive sampling of 100 respondents customers in starbucks coffee paragon mall surakarta criteria have made a purchase in starbucks more than three times. The data - data that has been analyzed quantitatively. Quantitative analysis in this study include: validity, reliability, normality test, multiple linear analysis and hypothesis testing via t test and F as well as the coefficient of determination (R2). From the results of the data that has been processed with SPSS for windows 17.0 obtained regression equation as follows: Y = - 0.946 + 0.266 X1 + 0.288 X2 + 0.444 + 0.474 X3 X4 X5 +0.686 Hypothesis testing via t test showed that all factors of experiential marketing has a significant impact on customer loyalty. Through the F test showed that the five independent variables is feasible to test the dependent variable in this study is customer loyalty. Figures R square of 0.601 in this study showed that 60.1% variation dependent variable customer loyalty can be explained by the fifth model in the regression equation. While the remaining 39.9% can be explained by the model - a model other than this study.